Forecasts on future evolution of artificial intelligence and intelligent systems - Radanliev, P; De Roure, D; Maple, C; Santos, O (Institute of Electrical and Electronics Engineers, 2022)
The field of artificial intelligence has gained a significant attention in the media. Some counties claim to be the leaders in the field, other countries claim to be winning in the race for leadership in artificial intelligence. This article conducts a statistical (i.e., bibliometric) analysis of research data records on artificial intelligence by year, country, language, and organisation. The results are clearly in favour of the USA on a national level, and English is clearly the dominant language for disseminating results. But in terms of leading organisation in the field of artificial intelligence creates more confusing result -between the Chinese Academy of Sciences and the University of California -in the leadership race.